Unusual self-inflicted foreign bodies in the urethra - Soumya Mondal,; Vishal Jalan,; Dilip Kumar Pal, (Indian Journal of Case Reports, 2021)
Self-inflicted urethral foreign body insertion in men is very rare and an important condition which urologists encounter in their clinical practice. Urologists should be familiar with the different techniques for the removal of these foreign bodies. Most cases are associated with psychiatric disorders. Hence, they should be referred for complete psychiatric evaluation. The emotional condition of the patient and the circumstances under which this act was committed should be investigated at the same time. Many cases of self-inflicted foreign body in the urethra have been reported in the literature such as fishhooks and bullets. However, metallic tongue cleaner in urethra has not yet been reported. Here, we are reporting the case of a 28-year-old male who presented with dysuria for 1 day following insertion of metallic tongue cleaner in the penile urethra, for sexual gratification which, he was unable to remove. The foreign bodies were found in the anterior urethra on X-ray and were successfully removed endoscopically without any complication. The patient was advised to take psychiatric consultation and counseling to prevent future episodes.